Selective inhibition of carbonic anhydrase IX and XII by coumarin and psoralen derivatives - Meleddu, Rita (J Enzyme Inhib Med Chem, 2021)
A small library of coumarin and their psoralen analogues EMAC10157a-b-d-g and EMAC10160a-b-d-g has been designed and synthesised to investigate the effect of structural modifications on their inhibition ability and selectivity profile towards carbonic anhydrase isoforms I, II, IX, and XII. None of the new compounds exhibited activity towards hCA I and II isozymes. Conversely, both coumarin and psoralen derivatives were active against tumour associated isoforms IX and XII in the low micromolar or nanomolar range of concentration. These data further corroborate our previous findings on analogous derivatives, confirming that both coumarins and psoralens are interesting scaffolds for the design of isozyme selective hCA inhibitors.